2022
DOI: 10.1007/s00234-022-02941-w
|View full text |Cite
|
Sign up to set email alerts
|

MRI detection of suspected nasopharyngeal carcinoma: a systematic review and meta-analysis

Abstract: Purpose Endoscopic biopsy is recommended for diagnosis of nasopharyngeal carcinoma (NPC). A proportion of lesions are hidden from endoscopic view but detected with magnetic resonance imaging (MRI). This systematic review and meta-analysis investigated the diagnostic performance of MRI for detection of NPC. Methods An electronic search of twelve databases and registries was performed. Studies were included if they compared the diagnostic accuracy of MRI to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Endoscopic biopsy is the gold standard for diagnosis of NPC. However, this examination method is invasive and it may miss some lesions generally attributed to submucosal location, coexistent hyperplasia, and difficult pharyngeal recess structure [ 30 , 31 ]. About 12% of NPC invisible under endoscopy can be successfully detected by MRI [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic biopsy is the gold standard for diagnosis of NPC. However, this examination method is invasive and it may miss some lesions generally attributed to submucosal location, coexistent hyperplasia, and difficult pharyngeal recess structure [ 30 , 31 ]. About 12% of NPC invisible under endoscopy can be successfully detected by MRI [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It had also detected 10% of hidden tumor from endoscopic view [ 44 ]. Another study with high sensitivity (98.1%) and specificity (91.7%) for lesion detection has suggested that MRI can be the primary diagnostic tool for NPC detection [ 45 ].…”
Section: Existing Limitation In Npc: Screening Diagnosis Treatment An...mentioning
confidence: 99%
“…NPC is usually diagnosed by nuclear magnetic resonance or CT imaging methods, as well as living sections of nasopharyngeal tissue. 6 Blood tests may also be used to detect antibodies to the Epstein-Barr virus (EBV). 7 According to the development of the disease, there are different methods for the treatment of NPC cells, such as surgery, radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms may be nonspecific and can be mistaken for other conditions, such as a respiratory infection or allergies. NPC is usually diagnosed by nuclear magnetic resonance or CT imaging methods, as well as living sections of nasopharyngeal tissue 6 . Blood tests may also be used to detect antibodies to the Epstein‒Barr virus (EBV) 7 .…”
Section: Introductionmentioning
confidence: 99%